Obesity and overweight by family type among freshmen of a private university of Lima: Obesidad y sobrepeso según tipología familiar de los estudiantes de una universidad privada de Lima - Alvines, Doris (2019)
Objective: determining the prevalence of obesity and overweight according to the type of family and the risk of acquiring non-communicable diseases (NCD).Materials and methods: Cross-sectional descriptive study. Participants were identified retroactively from students´ health cards. Obesity and overweight were determined basing on body mass index (BMI) and whereas for the risk of NCD waist circumference (WC) was used. Family type was classified as nuclear family, extended, expanded, single parent, reconstituted and family equivalent.Results: From 514 students, 43.4% were men and 56.6% women   (Mean age 20.7 years; min. 15; max. 50; DS= 5. 66). The predominant type of family was nuclear family represented by 52.1% (n = 268). In the classification according to BMI, 21.6% (n = 111) were overweight, 8.9% (n = 46) obese, with no evident differences between sexes (p = 0.257). According to the PA, the risk of acquiring NCD, 61.3% (n = 315) was low, 21% (n = 108) high and 17.7% (n = 91) had a very high risk. Both high and very high risk appeared in greater proportion among women, while low risk was presented among men (p< 0.001). No correlation between family type and BMI, nor NCD risks was found. Conclusions: The third part of the students presented excess weight. No relationship was found between the type of family and the BMI nor with the risk of suffering from NCD.   Keywords:  obesity, overweight, family (Source: MeSH, NLM)